PENINGKATAN HASIL BELAJAR ENGLISH VOCABULARY MELALUI PEMANFAATAN MEDIA FLASH CARD PADA PESERTA DIDIK KELAS IV SDI WOLOARA - Inanda Kartika Kahar; Agustina Pali; Stefanus Tebajak Henakin (Bajang Institute, 2024)
The problem in this research is that students' mastery of English vocabulary is still low. This research aims to describe improving English vocabulary learning outcomes through the use of flash card media for class IV students at SDI Woloara. This research is a type of classroom action research. The results of this research show that the use of flash card media can increase students' mastery of English vocabulary which can be seen in each cycle, namely in the pre-test it showed a result of 12.5%, then it began to increase in cycle I, namely 41.67% and experienced an increase in cycle II to 100 %. Thus, it can be concluded that the use of flash card media can improve the English vocabulary mastery of class IV SDI Woloara students.